Translating Protest: Networked Diasporas and Transnational Mobilisation in Ukraine’s Euromaidan Protests - Lokot, Tetyana; Boichak, Olga (PARTECIPAZIONE E CONFLITTO, 2022)
This study combines ethnographic and computational approaches to critically examine what gets ’lost in translation’ when studying intersecting social contexts of diasporic mobilisation around homeland politics. Considering how Ukrainians living in the U.S. engaged with homeland politics during the Euromaidan protests, we map transnational diasporic mobilisation, shining light on the various material, discursive, and affective connections that emerged in the process. We find that Euromaidan protests were a point of passage – and thus, convergence – between the often incongruous notions of national identity across regional as well as national territorial borders. Translating the local meanings and cultural codes associated with the Euromaidan protests, diasporas sought to amplify them to reach global audiences through their use of the grammars and vocabularies of socially mediated protest. Situating our inquiry in networked diasporic discourses and building on a decolonial understanding of Ukraine’s history and politics, our approach illuminates the possibilities for studying transnational mobilisation and activism as a heterogeneous network of publics, discourses, and identity practices.